Large Classes and the Application of the Seven Principles for Good Practice in Undergraduate Education - Ritchey, Lynn (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Many of us are expected to teach large introductory sociology courses. Traditionally, the teaching strategy for large classes has consisted of lecturing and formal examination of the material, usually in the form of multiple choice testing. University and college systems will always require the need for such courses. However, with careful thought and planning, large classes can incorporate the principles for good practice in undergraduate education. In 1987, Chickering and Gamson identified seven principles for good practice in undergraduate education. These practices are: 1. Contact between students and faculty. 2. Reciprocity and cooperation among students. 3. Use of active learning techniques. 4. Prompt feedback. 5. Emphasize time on task. 6. Communicate high expectations. 7. Respect of diverse talents and ways of learning. In this article, I will explore ways that faculty can design the large class environment to incorporate these principles.